History of Bank Indonesia Museum on Visitor Attraction - Pradini, Gagih; Awaloedin, Dipa Teruna; Agustiani, Fitri; Daely, Birgita Yunita R.C; Zifa, Maulita Syarifa; Ikhsani, Syifa Syaroh (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
Museum Bank Indonesia is a cultural institution that focuses on organizing, maintaining, and exhibiting collections related to Indonesia's economic and banking history. Located in Jakarta, this museum was established to capture the journey and development of the banking sector and economic policies in Indonesia. Understanding a nation's economic history involves not only historical facts, but also a deep understanding of the values, policies, and decisions that have shaped and still shape the economic direction of a nation. This understanding is an important foundation for achieving inclusive, sustainable, and equitable economic development. An understanding of economic history reveals how the distribution of wealth and people's well-being evolved. It can provide an understanding of economic inequality and its impact on daily life. Economic history reflects the role of the banking and financial sector in supporting economic development. This research method uses a qualitative approach